Should teachers be accurate or (overly) positive? A competitive test of teacher judgment effects on students' reading progress. (February 2022) - Förster, Natalie; Humberg, Sarah; Hebbecker, Karin; Back, Mitja D.; Souvignier, Elmar
Abstract: Previous findings on effects of teachers' judgments on student learning have been contradictory leading to the question of what kinds of judgments are most beneficial: accurate or (overly) positive ones? In this study, we provide the first competitive test of prominent but contradictory hypotheses regarding the consequences of teachers' judgments in the context of reading proficiency using reading fluency and reading comprehension performance judgments from 145 teachers and measures of real performance and learning progress across eight points of measurement from 2880 students. Response Surface Analyses combined with an information-theoretic approach for model comparison revealed no evidence of positive effects of judgment accuracy or overestimation of student performance by teachers. Instead, progress in reading fluency and reading comprehension was best predicted by students' prior achievement. For reading comprehension, the positivity of teachers' judgments was additionally beneficial: The higher a teacher judged a student's performance, the more the student learned. Highlights: The study compares competing hypotheses about the effects of teacher judgments. High teacher judgments are beneficial for students' reading comprehension growth. Teacher judgments do not affect students' reading fluency growth. Growth in reading fluency and comprehension was best predicted by prior performance. No evidence that accurate or overly positive teacher judgments are beneficial.